Multimodal Bin Picking System with Compliant Tactile Sensor Arrays for Flexible Part Handling - Muller, Veit; Elkmann, Norbert (Proceedings - IEEE International Conference on Robotics and Automation, 2019)
This paper presents a robot control architecture comprised of tactile and vision sensors incorporated into an off-the-shelf bin picking system. The proposed architecture facilitates flexible and reliable handling of objects and materials by employing a tactile grasp validation system and in-hand object monitoring. Two industrial grippers, specifically a magnetic gripper and a flexible vacuum gripper, are equipped with a compliant custom tactile sensor array. The algorithms used are for each specific gripper and respective sensor, however are transferrable to other grippers as well. The tactile sensing augments vision-based picking approaches, thus supporting in-hand object recognition [1] that is particularly useful for hard-to-recognize objects such as objects with transparent or shiny surfaces. Algorithms for tactile-based object pose estimation in the gripper and for grasp monitoring, including grasp validation, complete the approach.